Evaluating Land Cover Effects on Land Surface Temperature in the Juana Watershed for Urban Climate Adaptation - Endah Kurniyaningrum; Raihan Abdilla; Astri Rinanti; Liana Herlina; Giraldi Fardiaz Kuswanda; Kresna Dwiki Komara; Louis Wei Toffin; Simon Thieble; Muhammad Luthfi Assidik (Universitas Trisakti, 2026)
Aim: This study analyzes how land cover affects land surface temperature (LST). Understanding this helps optimize land management, improve agriculture, and address climate change impacts on soil temperature. Methodology and Results: To achieve this objective, the study employs a field experiment and remote sensing analysis to evaluate soil temperature variations. Land surface temperature data from Landsat satellite imagery enabled observation of the spatial distribution of soil temperature. The results indicate that sandy soils experience greater temperature fluctuations compared to clay soils, which are better at retaining heat over time. Conclusion, Significance, and Impact Study: This study confirms that soil texture and moisture content significantly influence land surface temperature dynamics. The findings can be applied to water management planning in the agricultural sector, climate change adaptation strategies, and more effective land use planning. The integration of remote sensing and field data improves the accuracy of large-scale soil temperature monitoring. Building on these results, future studies should specifically focus on quantifying the separate and combined effects of vegetation cover and organic matter content on soil thermal properties to further refine predictive models.